PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM - Prasetyo, Gusniar Resty (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is performed with the purpose to analyze the influence of financial performance to the stock price athotel and tourism companies which are listed in Indonesia Stock Exchange (IDX). Afterwards, this research alsoanalyzes the difference for the companyâs stock price whether it is in healthy and unhealthy category. The collectionof research samples is performed by using purposive sampling method and 15 companies have been selected assamples during 3 years research periods (2010-2012). The simple linear regression is used as statistics method inorder to examine the influence of financial performance (it is measured by using Discriminant Altman model) to thestock price, and Mann-Whitney test which is used to analyze the stock price difference to the category of financialhealth. The result of research shows that the financial performance has significant influence to the stock price, and ithas been known that there is stock price difference for company with healthy and unhealthy category.Keywords: Z-Score, category of financial health, stock price